Language as Scientific Instrument: a Preliminary Digital Analysis of Christiaan Huygens' Last Writings and Correspondence - Marinucci, Ludovica (JLIS.it, 2018)
This essay focuses on a digital text analysis with AntConc computational linguistics tool in order to find, list and compare the most important key word occurrences and their collocations in some of Christiaan Huygens last writings, from 1686 to 1695 and posthumous. The greatest attention is payed to three key words – Animus, Potentia and Lex – related to the themes of God’s power, divine and human intelligence, probabilistic epistemology, natural theology and plurality of worlds. In addition, these key words are used to select the letters written by Huygens to the most important of his contemporaries on the same topics. This challenge firstly involves demonstrating that his last writings on philosophical and theological reflections on mechanistic philosophy are not an anomaly within Huygens’ wider work, and secondly showing that these are indications of Huygens’ involvement in a number of theoretical debates in the second half of the seventeenth century.